Community-Care Approach for Social Work Practice: Learning from Community-Based Healthcare for Elderly in Yogyakarta - Tri Winarni Soenarto Putri; Kafa Abdallah Kafaa; Tauchid Komara Yuda (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
This article aims to demonstrate the application of a community-care approach in the provisioning of elderly social and health care services (hereafter, social-health care) through a case study at Elderly Family Development (Bina Keluarga Lansia–BKL) Mugi Waras in Sumbersari Village, Sleman Regency, Special Region of Yogyakarta Province. This institution was chosen as a case study since it represents the best community-based long-term social-health care institution for the elderly in Indonesia. Based on the findings that have been analyzed, it was concluded that there has been shifting of institutional care provision in the community care regime towards more inclusion with mixed welfare features. This may have occurred because BKL was suffering from the lack of resources they have in dealing with the increased needs of the elderly and increased risk. Consequently, even though the influence of external stakeholders in this initiative appears quite strong, such a community-centered care initiative can be continually maintained and resulted in the hybridization model of a care regime. For social worker’s practitioner insight, the paradigm of program implementation in the BKL Mugi Waras can be adopted as a community-based social work practice that appears to fit developing countries, where elderly service intervention should be fine-tuned to the elderly residents’ living arrangements.